Application and utilization of fermentation as a processing tool to mitigate protein putrefaction in plant-based diets - Panapparambil Sooraj, Ihsaan; Leech, John; O’Callaghan, Tom F.; McAuliffe, Olivia (Frontiers in Microbiology, 2025)
There is an evolving interest in the adoption and incorporation of plant proteins in Western diets as sustainable alternatives to meat consumption. This is typically motivated by the environmental and public health concerns posed by animal-based diets. However, plant proteins have been demonstrated to exhibit reduced bioavailability as a consequence of high concentrations of anti-nutritional factors (ANFs) and complex protein structures, leading to incompletely digested protein reaching the colon. This undigested protein undergoes microbial putrefaction, generating metabolites like ammonia, phenols, and hydrogen sulfide that are potentially associated with inflammation, gut barrier dysfunction, and chronic diseases. Literature searches utilizing tools such as Google Scholar and PubMed were performed with identifying relevant work in both putrefaction and fermentation, to highlight gaps for future research. There is evidence that including a microbial fermentation step in the processing of plant proteins can degrade ANFs, hydrolyze protein structure, and increase free amino acids, thereby improving upper gastrointestinal digestibility. The application of fermentation strategies can address both nutritional and safety challenges by pre-digesting proteins and enriching functional metabolites such as SCFAs and polyphenols. However, gaps persist in understanding many elements of fermentation of plant proteins including microbial consortia optimization, in vivo impacts, and long-term health outcomes. This review examines protein putrefaction in the gut and its association with adverse health impacts, and furthermore, fermentation is evaluated as a potential processing aid for plant proteins to enhance digestibility and mitigate putrefaction risks.